ANALYSIS OF BAWASLU'S AUTHORITY IN HANDLING ELECTION VIOLATIONS AFTER THE DETERMINATION OF ELECTION RESULTS ACCORDING TO JURIDICAL AND FIQH SIYASAH DUSTURIYAH - Hidayat, Rahmat; Maghfira, Saadatul; Efendi, Roni; Utamy, Hebby Rahmatul (Hukum Islam, 2023)
The focus of the research is the authority of Bawaslu in dealing with election violations after the determination of election results nationally according to Law Number 7 of 2017 concerning General Elections and how the fiqh dusturiyah fiqh review of the authority possessed by Bawaslu. This research is normative legal research. Based on the results of the research, it can be explained that Bawaslu in dealing with election violations after the determination of election results nationally in its implementation raises a separate problem because Bawaslu is very likely to issue decisions that can have implications for changes in the results of the votes acquired by election participants if the handling of violations is carried out after the determination of national election results. The practice of implementing Bawaslu's authority in dealing with violations that have an impact on the results of the vote acquisition after the determination of the national election results conflicts with the authority of the Constitutional Court so that it allows for overlapping of the authority of Bawaslu in following up on alleged election violations with the authority held by the Constitutional Court to resolve disputes over General Election Results Disputes (PHPU). The fiqh siyasa dusturiyah review of the authority of Bawaslu is not by the values in the Qur'an and fiqh siyasa dusturiyah related to the study of al-hisbah as an institution authorized to carry out supervision aimed at realizing amar ma'ruf nahi munkar which in principle is to bring benefits and reject mafsadat.